Pengolahan Limbah Cair Industri dari PT. Sier Menggunakan Metode Elektroflotasi (EF) - Dionysius Nathanael; Keenan Michael Agape; Adriana Anteng Anggorowati; Andrew Joewono (Widya Teknik, 2021)
One of the methods for treating industrial waste is using the electro-flotation (EF) method. In this study, the EF method used requires stainless steel as the anode and aluminum as the cathode. Industrial wastewater treated using the EF method comes from PT. Surabaya Rungkut Industrial Estate (SIER). Liquid waste is put into the EF basin, then the power supply is turned on and then the voltage and contact time are adjusted. After the EF process, the treated wastewater was sampled in a certain amount to measure the value of Chemical Oxygen Demand (COD), Total Suspended Solid (TSS) and the number of bacterial colonies. Based on the calculation, the result shows that with an electric voltage of 32.5 volts and a contact time of 60 minutes, the result is the largest decrease in COD and TSS values. COD decreased from 236.66 mg / L to 24.56 mg / L or 90%, TSS decreased from 187 mg / L to 34.33 mg / L or 81.64%. While the decline in bacterial colonies from 4,7.104   to 4,03.103  or 91,42% decrease at the mains voltage of 19 volts and contact time for 20 minutes.